1999
DOI: 10.1302/0301-620x.81b5.9545
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative bacterial contamination in operations for joint replacement

Abstract: All surgical operations have the potential for contamination, and the equipment used can harbour bacteria. We collected samples from 100 elective primary hip and knee arthroplasties. These showed rates of contamination of 11.4% for the sucker tips, 14.5% for light handles, 9.4% for skin blades and 3.2% for the inside blades used during surgery; 28.7% of gloves used for preparation were also contaminated. Of the samples taken from the collection bags used during hip arthroplasty, 20% grew bacteria, which repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
97
2
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(111 citation statements)
references
References 15 publications
8
97
2
3
Order By: Relevance
“…In short, there is substantial evidence to state that positive cultures could be caused by non-detected contamination during the stages of harvesting, storage or their manipulation before implantation. Davis and colleagues [5] studied the contamination rates in samples from the surgical suckers, bladders and needles; the organisms and contamination rates found were similar to those in our study (skin commensals) and the rate of infection was 1% (with the infecting organism different from that found in the surgical instruments). Our results show that contamination of the allografts in the operating theatre is as frequent as the contamination of the surgical equipment.…”
Section: Discussionsupporting
confidence: 83%
“…In short, there is substantial evidence to state that positive cultures could be caused by non-detected contamination during the stages of harvesting, storage or their manipulation before implantation. Davis and colleagues [5] studied the contamination rates in samples from the surgical suckers, bladders and needles; the organisms and contamination rates found were similar to those in our study (skin commensals) and the rate of infection was 1% (with the infecting organism different from that found in the surgical instruments). Our results show that contamination of the allografts in the operating theatre is as frequent as the contamination of the surgical equipment.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, positive cultures could be caused by non-detected contamination at harvesting, storing or during manipulation before implantation. Davis et al [6] found similar contamination rates to us in samples taken from the sucker tips, light handles, blades and needles used in 100 elective primary hip and knee arthroplasties. Organisms found were similar to those in our study (skin commensals) and the rate of infection was 1% (with the infecting organism different from the single identified contaminant) [6].…”
Section: Discussionsupporting
confidence: 70%
“…We think that the contamination of these allografts happened while processing them for implantation in the operating theatre, as has already been reported with surgical needles and suckers [6]. In any case, as we have shown in our series, this contamination has no clinical relevance if antibiotic prophylaxis is used.…”
Section: Discussionsupporting
confidence: 65%
“…Several studies have demonstrated that equipment contamination can occur during surgery (90)(91)(92)(93)(94). Givissis et al investigated the contamination rate of suction tips and tried to correlate it with the development of subsequent deep wound infection (91).…”
Section: Medical Equipmentmentioning
confidence: 99%